Effects of a functional food supplemented with probiotics on biological factors related to dental caries in children: a pilot study (2019)
Purpose The aim of this study was to evaluate the effects of a functional food supplemented with probiotics on biological factors related to dental caries in children aged 3–5 years. Methods A repeated measures pilot study was conducted with children who have consumed a commercial milk containing two lactic acid bacteria as probiotics (WP milk) for a period of 3 months and another period of 3 months consuming a milk without probiotics (NP milk). Salivary pH, plaque index, pH variation before and after a sugar rinse, quantification of Streptococcus mutans in saliva and demineralisation of the carious lesions were determined at the beginning and at the end of both milk ingestion periods. Results Regarding WP milk, a non-significant decrease in terms of the concentration of S. mutans and pH variation (p > 0.05), a significant decrease (i.e. acidification) in salivary pH (p < 0.01) and a remineralisation of 39.4% of the caries were found. On the other hand, for NP milk, a non-significant increase in terms of the concentration of S. mutans, pH variation, salivary pH (p > 0.05) and a remineralisation of 64.2% were found. Conclusions Lactic acid probiotics can contribute to the decrease in the number of cariogenic microorganisms. However, the appropriate selection of the bacteria type with regard to its acidogenicity is fundamental to avoid the generation of an effect contrary to that expected, e.g. a significant decrease in salivary pH.